Factors affecting staff’s operational success in Finance Department, Xayabouly province - sithavong, vilayphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aimed to examine the factors affecting staff operational success in the Finance Department of Xayabouly Province. The objective was to identify key motivational and maintenance factors that influence employees' performance. The sample consisted of 54 employees from the department. Data were collected through questionnaires and analyzed using statistical software. The study found that motivational factors identified as highly significant included: achievement in work and enthusiasm for assigned tasks; responsibility being able to complete work within the given timeframe; recognition being trusted with assigned tasks; the nature of work alignment with personal skills and knowledge; and career advancement receiving support for professional growth. Maintenance factors also played a crucial role. The most important was the relationship with colleagues, particularly unity and cooperation within the unit. This was followed by working conditions, such as understanding of duties; command and control, especially managers' willingness to listen to employee feedback; compensation, including position and administrative allowances; and policies and administration, notably welfare policies like vacation, maternity leave, and sick leave. Regarding factors affecting operational success, the study identified three independent variables with a statistically significant impact: respect (X2), progress (X5), and compensation (X10). These variables together could predict 76.90% of the variance in employee operational success (Adjusted R² = 0.769).